OPTIMISME EKONOMI NELAYAN DI TENGAH PERGOLAKAN POLITIK SULAWESI SELATAN 1954-1965 - Rifal Najering (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2018)
This article discusses the optimism of economic life economy of people in the midst of political unrest in Southern Sulawesi, especially the village of Gusung, Makassar. In general, the political process of political affairs would affect all the joints in the lives of society, political influence on economic life, social even culture. During the period after independence, particularly the events of political turmoil, nearly practically influenced the lives of people on land and sea. But this type of thesis to be reconsidered in the history of the local fishermen in the village of Gusung. During the same period were found in the economic activity of the fisherman society has an effect to life on land. It can be seen from the distribution of a region of fish that was found in Gusung village nearly all came from the west coast and part of the east coast of Sulawesi, at that time was turbulent by political turmoil. In 1960, a region like Maros, Pangkajene, Tanete, Tanah Keke, Segeri, Talakasi, most of Makassar islands and Pare-pare became the largest area of fish suppliers in the village of Gusung. The catch of fishermen in the village of gusung that are marketed until Manado, Surabaya, and Jakarta. In the midst of â€œpolitical turmoilâ€ can be found by a group of societies that are celebrating the commercial economy. This study is a study of history with a qualitative approach. Data obtained through interviews with fishermen and the local interpreneurs and the source of the written source is especially in inventory of the ujung pandang municipal. Next, data is provided by using the history method, the heuristic, criticism, interpretation and historiography.